(untitled) (The Lumbini Journal of Business and Economics, 2026)
Purpose: While contemporary practices in entrepreneurship pedagogy have departed from traditional methods towards learner-centered approaches such as simulation, we discovered that physical startup simulation has got limited attention in scholarly literature, prompting us to conduct an empirical study to explore it further. Methods: This phenomenological study employed qualitative design to explore the perceptions about ‘physical startup simulation’ from 11 MBA students, selected using a purposive sampling technique, representing four different academic institutions of Bagmati Province in Nepal. The qualitative data was collected using unstructured interviews that was later transcribed and translated into English to conduct thematic analysis. Results: The empirical findings generated four major themes: pedagogical innovation, startup management skills, startup risk management, and feedback-based learning and motivation. These themes align with Kolb’s experiential learning theory and Ries’s lean startup theory. Based on these themes, we propose a novel physical startup simulation model that holds practical relevance for entrepreneurship educators in developing entrepreneurial competencies among students. Conclusion: We contrast our simulation model with software-based digital simulation and argue that our model presents a more effective, logistically simpler, and economical (even by the standards of the least developed countries) pedagogical tool relevant to entrepreneurship education and pedagogy.